Efforts to Increase The Learning Effectiveness of Throwing Disc Using Plastic Plate Modification Media in Student Class VI SDN 01 Semitau Lesson Year 2014/2015 - Achmad Samiun (Universitas Tanjungpura, 2018)
The purpose of this Classroom Action Research is to find out how far media modification of plastic plates can improve the effectiveness of learning Throw Discs in class VI SD Negeri 1 Semitau. This research uses action research for three rounds, each round consists of four stages: design, activity and observation, reflection, and revision. The target of this research is Semitau State Elementary School Semitau Sub-District Semitau Kapuas Hulu District Year 2014-2015. Data obtained in the form of observation, observation sheet of teaching and learning activities.